Advanced Ophthalmic Drug Delivery Systems and AI-Assisted Drug Discovery: Current Progress and Future Perspectives - Srinivas Dommeti,; Seetharam Gude, (Public Health, 2026)
Ophthalmic drug development remains one of the most challenging areas in pharmaceutical research due to the complex anatomy and protective barriers of the eye. Conventional ocular dosage forms, particularly topical formulations, often exhibit poor bioavailability because of rapid tear turnover, blinking, nasolacrimal drainage, and limited corneal permeability. These limitations reduce therapeutic efficiency and necessitate frequent dosing, ultimately affecting patient compliance. In recent years, significant advances have been achieved in the development of innovative ocular drug delivery systems, including ocular implants, hydro- gels, nanoparticles, nanomicelles, liposomes, microneedles, iontophoresis, in situ gels, and drug-eluting contact lenses. These technologies aim to improve drug retention, enhance tissue penetration, and provide sustained therapeutic effects for both anterior and posterior segment eye diseases. Simultaneously, artificial intelligence (AI) and digital technologies are transforming ophthalmic drug discovery and development by accelerating target identification, molecular screening, biomarker analysis, and formulation optimiza- tion. AI-driven approaches such as machine learning, deep learning, explainable AI, and large language models have shown considerable potential in reducing development timelines and improving predictive accuracy. In addition, additive manufacturing technologies, including three-dimensional printing and hot- melt extrusion, have enabled the development of personalized ophthalmic devices and customized drug delivery systems. Despite these advances, several challenges remain, including manufacturing complexity, regulatory uncertainties, scalability issues, data privacy concerns, and the absence of harmonized global guidelines for AI-assisted therapeutics. This review highlights recent developments in advanced ocular drug delivery systems, emerging AI-based technologies, regulatory perspectives, and future opportunities aimed at improving the treatment of complex ocular diseases and reducing the global burden of visual impairment.